Impact of ASEAN Free Trade Area and ASEAN Economic Community on Intra-ASEAN Trade - Wong, Colin Koh King (2010)
This study aims to examine the impact of the implementation of ASEAN Free Trade Area (AFTA) and the announcement of ASEAN Economic Community (AEC) on the intra-regional trade between the ASEAN member countries and their trading partners at aggregate level as well as at sectoral level, namely the agro-based and manufacturing sectors. The empirical findings show that the implementation of AFTA and the announcement of AEC, as well as sectoral-based trade play important roles in attracting trade between ASEAN member countries. In terms of relative importance of sectoral level, the empirical results show that intra-trade for manufacturing sectors are more significant than the agro-based sectors. Also, the study also examines the role of the three major global players, namely the US, Japan and China, in influencing the intra-regional trade between ASEAN member countries. This further proves that the three major global players (United States, Japan and China) also demonstrate important roles in stimulating trade between the ASEAN member countries. The gravity model with panel data estimation is employed and the sample countries consist of ASEAN 5 and its forty primary trading partners. From the basic gravity variables, the empirical results find that GDP, population, relative endowment, distance and common language are the major determinants of bilateral trade in ASEAN.